2015
DOI: 10.3390/met5010457
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Characterization of the Microstructures and Tensile Properties of As-Cast and Thixoforged in situ AM60B-10 vol% Mg2Sip Composite and Thixoforged AM60B

Abstract: Abstract:The microstructure and tensile properties of the thixoforged in situ Mg2Sip/AM60B composite were characterized in comparison with the as-cast composite and thixoforged AM60B. The results indicate that the morphology of α-Mg phases, the distribution and amount of β phases and the distribution and morphology of Mg2Si particles in thixoforged composite are completely different from those in as-cast composite. The Mg2Si particles block heat transfer and prevent the α-Mg particles from rotation or migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…When the PTF alloy was subjected to solution treatment at 560ºC for 3h, lots of flat facets that resulted from cracks propagating across primary α-Al phases appeared (Fig.9b). This indicated that the fracture of PTF alloy may follow a transgranular mode at this time, which was a sign of improved tensile strengths for the thixoformed materials 22,25 . Besides, the amount of the dimples became less but its size was observed to be larger than the as-fabricated state, suggesting an improvement in the elongation of the PTF alloy after solution treatment.…”
Section: Influence Of Solution Temperature On Tensile Propertiesmentioning
confidence: 90%
“…When the PTF alloy was subjected to solution treatment at 560ºC for 3h, lots of flat facets that resulted from cracks propagating across primary α-Al phases appeared (Fig.9b). This indicated that the fracture of PTF alloy may follow a transgranular mode at this time, which was a sign of improved tensile strengths for the thixoformed materials 22,25 . Besides, the amount of the dimples became less but its size was observed to be larger than the as-fabricated state, suggesting an improvement in the elongation of the PTF alloy after solution treatment.…”
Section: Influence Of Solution Temperature On Tensile Propertiesmentioning
confidence: 90%
“…Therefore, the UTS of the thixoforged AM60B decreases at 150 °C owing to the absence of a reinforcing phase for the matrix (Figure 2). As mentioned above, the Mg2Si particle always locates in the last solidified regions [20], i.e., surrounded by the eutectic phase. Thus, the softening of the eutectic β phase leads to the decrease in the interfacial bonding strength between the Mg2Si particles and the matrix.…”
Section: Tensile Properties Of the Thixoforged Composite At Differentmentioning
confidence: 99%
“…This can be achieved by alloying and by the addition of particles formed in-situ and ex-situ [4][5][6]. New processes are also entering the manufacturing scene affording new possibilities to create novel microstructures and thereby also new types of property combinations [6,7]. The introduction of new processes also shifts the boundary between processes that used to be made in fully solid state and now move towards casting and more liquid processing resulting in hybrid processes [6][7][8].…”
mentioning
confidence: 99%
“…New processes are also entering the manufacturing scene affording new possibilities to create novel microstructures and thereby also new types of property combinations [6,7]. The introduction of new processes also shifts the boundary between processes that used to be made in fully solid state and now move towards casting and more liquid processing resulting in hybrid processes [6][7][8]. Independent of this, post treatment processes for bulk and surface properties are still needed to be used together with the novel processing property capability [8,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation